An integrative review on mothers' experiences of online breastfeeding peer support: Motivations, attributes and effects - Hyojeong Moon; Kyungmi Woo (Maternal and Child Nutrition, 2021)
Abstract Information on the experiences surrounding online breastfeeding peer support among breastfeeding mothers and its effects on breastfeeding outcomes is growing yet to be synthesized. The aim of this review was to synthesize the evidence of mothers' experiences of online breastfeeding peer support. An integrative review was conducted. Five electronic databases were searched. Two reviewers independently screened the articles for inclusion. The inclusion criteria were (1) involved original data focusing on mothers' experiences of online breastfeeding peer support, (2) participants who were mothers who were breastfeeding or had experiences of breastfeeding and (3) studies focusing on interaction and communication among mothers through online communities. In total, 14 publications met the inclusion criteria. Breastfeeding mothers turned to online groups when they felt isolated, lacked professional support or preferred online support over face‐to‐face support. Online breastfeeding peer support was characterized as a virtual community, with easy access, availability and a wealth of resources from actual experiences of mothers. It empowered breastfeeding mothers and resulted in changes in breastfeeding outcomes and perceptions. The positive aspects of online breastfeeding peer support have recently garnered more attention. This review provided baseline data and evidence to supplement and improve the current breastfeeding support system for breastfeeding mothers. The evidence on the effectiveness of online breastfeeding peer support for influencing breastfeeding outcomes remains inconclusive. Further empirical studies with rigorous study designs are warranted.